2016
DOI: 10.1080/03004430.2016.1226355
|View full text |Cite
|
Sign up to set email alerts
|

Talking everyday science to very young children: a study involving parents and practitioners within an early childhood centre

Abstract: The acquisition of everyday scientific concepts by 3-6 year old children attending early childhood institutions has been widely studied. In contrast, research on science learning processes among younger children is less extensive. This paper reports on findings from an exploratory empirical study undertaken in a 'stay and play' service used by parents with children aged 0-3 and located within an East London early childhood centre. The research team collaborated with practitioners to deliver a programme of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The study found that parental interaction enhanced the children's learning at least as much, if not more than practitioner interventions. Based on this finding Lloyd et al [27] highlight the significance of "familiar" adults in mediating young children's enjoyment and encouraging natural curiosity.…”
Section: The Teaching Of Science Concepts (Pedagogical Practices): Bi...mentioning
confidence: 97%
See 2 more Smart Citations
“…The study found that parental interaction enhanced the children's learning at least as much, if not more than practitioner interventions. Based on this finding Lloyd et al [27] highlight the significance of "familiar" adults in mediating young children's enjoyment and encouraging natural curiosity.…”
Section: The Teaching Of Science Concepts (Pedagogical Practices): Bi...mentioning
confidence: 97%
“…The literature review identified 1 study [27] in which science concept formation was examined in relation to pedagogical practices, in children aged birth to three years. This study is now discussed.…”
Section: The Teaching Of Science Concepts (Pedagogical Practices): Bi...mentioning
confidence: 99%
See 1 more Smart Citation
“…She investigates these by touching, tasting and smelling -she now tries to make artificial puddle in her garden with soil and water, in the kitchen with flour, custard powder and milk, in school with Playdough and 'slime', she is continually testing different materials that, more or less, looks like a puddle but taste, smell and feel different. These young children are self-curious, exhibiting the development of enquiry skills, anxious to learn about the environment, trying to mimic their elders and exhibit a capacity to build their learning further through adults support (such as parents, siblings, peers, teachers), media, nature, society and culture (Lloyd et al, 2017).…”
Section: Teaching Science Through Stories: Mounting Scientific Enquiry Introductionmentioning
confidence: 99%
“…She investigates these by touching, tasting and smelling -she now tries to make artificial puddle in her garden with soil and water, in the kitchen with flour, custard powder and milk, in school with Playdough and 'slime', she is continually testing different materials that, more or less, looks like a puddle but taste, smell and feel different. These young children are self-curious, exhibiting the development of enquiry skills, anxious to learn about the environment, trying to mimic their elders and exhibit a capacity to build their learning further through adults support (such as parents, siblings, peers, teachers), media, nature, society and culture (Lloyd et al, 2017).The question is how we can strengthen this scientific enquiry among children from early year's foundation stage (EYFS) with an aspiration to develop further over time? So that, Aslan, Milly and Sarah and many other children like them, not necessarily will become practising scientists in the future, but it is hoped that these children will adapt a scientific attitude.…”
mentioning
confidence: 99%